Optical properties of a periodic monolayer of metallic nanospheres on a dielectric waveguide - G. Gantzounis; N. Stefanou; V. Yannopapas (Journal of Physics: Condensed Matter, 2005)
The optical properties of a dielectric waveguide coated on one side with a periodic monolayer of metallic nanospheres are studied by means of transmission and density-of-states calculations using the on-shell layer-multiple-scattering method. In particular, the strong coupling mechanism between the waveguide and collective particle–plasmon modes is analysed and its influence on the optical response of the system is elucidated.